P35 Histiocytoid cardiomyopathy and microphthalmia with linear skin defects syndrome: Phenotypes linked by truncating variants in NDUFB11. (2nd March 2016) - Rea, Gillian; Ware, James S; Homfray, Tessa; Till, Jan; Roses-Noguer, Ferran; Buchan, Rachel; Wilkinson, Sam; Wilk, Alicja; Walsh, Roddy; John, Shibu; McKee, Shane; Stewart, Fiona J; et al.
Abstract : Mutations in NDUFB11, which encodes a component of the Mitochondrial Respiratory Chain (MRC) were recently reported to cause both Histiocytoid Cardiomyopathy (Histiocytoid CM) and Microphthalmia with Linear Skin Defects Syndrome (MLS syndrome). Histiocytoid CM is a rare, distinctive form of cardiomyopathy with ˜ 150 cases reported worldwide, that predominantly affects females early in life and is characterised by arrhythmias and associated sudden death. MLS syndrome, also known as a MIDAS (microphthalmia, dermal aplasia, and sclerocornea) syndrome, is a rare X-linked disorder with male lethality in utero, characterised by unilateral or bilateral microphthalmia and linear skin defects, along Blaschko lines, which are classically limited to the face and neck, present from birth, and heal with time, often leaving minimal scarring. Here we report a fourth case of Histiocytoid CM with a de novo nonsense mutation in NDUFB11 (ENST00000276062.8: c.262C >T;p. Arg88Ter), identified using Whole Exome Sequencing (WES) of a family trio. An identical mutation has been previously reported in association with MLS syndrome. Our case lacked the diagnostic features of MLS syndrome but detailed clinical comparison of the two cases revealed significant phenotypic overlap. Heterozygous mutations in HCCS and COX7B, which, like NDUFB1, encode proteins of the MRC, have also previously been identified in MLS syndrome including a case with features of both MLS syndrome and Histiocytoid CM. However, a systematic review of WES data from previously published Histiocytoid CM cases, alongside four additional cases presented here for the first time, did not identify any mutations in these genes. We conclude that that NDUFB11 is a cause of both Histiocytoid CM and MLS, and that these disorders are allelic (genetically related). Screening for evidence of malignant arrhythmias and cardiomyopathy would be appropriate in individuals with MLS syndrome.